2021
DOI: 10.7717/peerj.11485
|View full text |Cite
|
Sign up to set email alerts
|

Run for your life: can exercise be used to effectively target GLUT4 in diabetic cardiac disease?

Abstract: The global incidence, associated mortality rates and economic burden of diabetes are now such that it is considered one of the most pressing worldwide public health challenges. Considerable research is now devoted to better understanding the mechanisms underlying the onset and progression of this disease, with an ultimate aim of improving the array of available preventive and therapeutic interventions. One area of particular unmet clinical need is the significantly elevated rate of cardiomyopathy in diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 198 publications
(245 reference statements)
0
2
0
Order By: Relevance
“…Moreover, 6 weeks of concentric RET (loaded ladder climbing) increased GLUT4 expression in diabetic mice (Dehghan et al 2016 ). Several studies demonstrated that LICET also increases GLUT4 expression in both skeletal and cardiac muscle (Bowman et al 2021 ). Additionally, 6 weeks (3 week −1 ) of 4–6 sets of 30-s maximal bicycling increased muscle GLUT4 content by ~ 20% compared to baseline in healthy men (Burgomaster et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 6 weeks of concentric RET (loaded ladder climbing) increased GLUT4 expression in diabetic mice (Dehghan et al 2016 ). Several studies demonstrated that LICET also increases GLUT4 expression in both skeletal and cardiac muscle (Bowman et al 2021 ). Additionally, 6 weeks (3 week −1 ) of 4–6 sets of 30-s maximal bicycling increased muscle GLUT4 content by ~ 20% compared to baseline in healthy men (Burgomaster et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin sensitivity has been increased in elderly men following a single session of eccentric RET per-week for 12 weeks, whereas concentric RET did not produce equivalent results (Chen et al, 2017). Further research conducted in alternative populations, including diabetic and healthy adults, implies that exercise reliant on high muscle glucose metabolism may be more efficacious in elevating GLUT4 expression, supporting the implementation of both high-intensity interval (Burgomaster et al, 2007) and low-intensity continuous (Bowman et al, 2021) endurance exercise, in addition to concentric RET (Dehghan et al, 2016). The obvious issue in implementing an intervention aimed at maximising glucose metabolism is a higher energy yield is undesirable in the cachectic individual.…”
Section: Benefits Of Exercisementioning
confidence: 97%